Framework Design Thinking as a Teacher Competences - Purwasih, Desy; Wilujeng, Insih; Wiyarsi, Antuni; Zakwandi, Rizki (KnE Social Sciences, 2024)
The ability to produce creative solutions is currently needed due to rapid social, technological, and economic changes. Stakeholders can bring together various points of view to produce comprehensive solutions. Design thinking offers an inventive approach to solving challenging problems. This research offers a comprehensive perspective and understanding of design thinking as a framework for measuring the abilities of prospective teachers. A qualitative approach with documentary content analysis methodologies produces a theoretical competency framework. The findings are then applied to pinpoint design thinking’s dimensions and indicators as pertinent competencies, such as empathy, experimentation, optimism, feedback seeking, and collaboration. These results significantly advance our knowledge of how, in the present environment, design thinking may be understood, utilized, and assessed as a critical talent. Considering the increasingly complex and dynamic characteristics of education, this research emphasizes the importance of building design thinking competencies for prospective teachers. Keywords: assessment, conceptual framework, design thinking, teacher education